2020
DOI: 10.1021/acs.cgd.0c00113
|View full text |Cite
|
Sign up to set email alerts
|

Structural Extension from 0D to 3D Pillared Heterometallic 3d-4f Polyoxometalate Hybrids

Abstract: Four 3d−4f heterometallic pillared polyoxometalate hybrids, namely, [Ln 2 Cu(SiW 12 O 40 )(Hina) 4 4) Eu (3), (5), Hina = isonicotinic acid), were synthesized under hydrothermal conditions inspired by a structure of zero-dimensional (0D) Tb-based polyoxometalate [Tb 2 (ina) 2 (Hina) 6 (H 2 O) 2 ](SiW 12 O 40 ) (1). Structural analysis of 1 reveals that all the N atoms of ina ligands are uncoordinated and can serve as potential coordination sites to bridge transition metals. So, the copper cation was introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Polyoxometalates (POMs) are a class of very important photochromic materials due to their good redox properties and photoactivity, and readily undergo photoinduced electron transfer to form Mo/W(V)-containing heteropolyblue. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] In general, purely inorganic POMs have poor photochromic behavior and are difficult to synthesize, while purely organic photochromic materials have poor fatigue resistance and high temperature resistance despite their fast response and rich color, 30,31 so it has been difficult to find new photochromic materials in pure organic or inorganic systems. By contrast, organic-inorganic hybrid photochromic materials can not only maintain or even enhance the properties of the respective components, but also generate new properties based on the synergistic effect between the components, which is more attractive to researchers.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Polyoxometalates (POMs) are a class of very important photochromic materials due to their good redox properties and photoactivity, and readily undergo photoinduced electron transfer to form Mo/W(V)-containing heteropolyblue. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] In general, purely inorganic POMs have poor photochromic behavior and are difficult to synthesize, while purely organic photochromic materials have poor fatigue resistance and high temperature resistance despite their fast response and rich color, 30,31 so it has been difficult to find new photochromic materials in pure organic or inorganic systems. By contrast, organic-inorganic hybrid photochromic materials can not only maintain or even enhance the properties of the respective components, but also generate new properties based on the synergistic effect between the components, which is more attractive to researchers.…”
Section: Introductionmentioning
confidence: 99%
“…[39] Two competing concentration effects may occur when La 3 + ions were doped into EuW 10 . [11] The effective content of Eu 3 + ions (luminescence center ions) decrease with the increase of the relative content of La 3 + ions, which leads to the decrease of the luminescence intensity. Meantime, the 4 f orbital of the La 3 + ions are empty with no f-f transition, thus no electrons are excited.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature sensing mechanism of temperature-sensitive paints: Generally, excited state molecules return to the ground state through the process of radiation (k r ) and non-radiation (k nr ), and the non-radiation process is the key to the temperature sensing performance (Figure 8). [11] Probe molecules are excited by absorbing energy and collide with other particles. The collision behavior converts part of the energy into heat.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent work, we showed that a number of tartratocuprate complexes with defined structures can be assembled. [34][35][36][37] For instance, the use of guanidinium cations as structure directing agents (SDAs) and multiple ligands gives rise to 2D-layered frameworks {Cu II 32 } n and complex clusters {Cu II 48 }, respectively (Fig. 1).…”
mentioning
confidence: 99%